'More-than-human' resilience(s)? Enhancing community in Finnish forest farms. (February 2016) - Herman, Agatha
Highlights: I explore community resilience amongst Finnish farmers. The forest is used to explore the role of the more-than-human in social resilience. More-than-human resilience can be seen as an emergent network property. The more-than-human establishes resilience as relational, contextual and multiple. Recognising the social as co-fabricated fosters a more just resilience.